2011
DOI: 10.2174/157016311795563820
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Decreases Therapeutic Efficacy in Colon Cancer Cell Line HT29 Via the Activation of the PI3K/Akt Pathway

Abstract: Obesity has been associated with both the carcinogenesis and poor prognosis of colon cancer, one of the leading causes of cancer-related death. Increased blood levels of insulin in obese subjects have been demonstrated to play a key role in carcinogenesis. It is also possible that insulin affects treatment efficacy, leading to poor prognosis. In this study, we demonstrated that insulin can increase HT29 colon cancer cell line resistance to cycloheximide and 5-fluorouracil induced cytotoxicity. This effect can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
1
27
0
4
Order By: Relevance
“…Thus it can be speculated that patients with obesity might exhibit an impaired response to chemotherapy, particularly protocols that include targeted therapies. In addition, in some patients with obesity, increased plasma levels of insulin may further decrease therapeutic effect 88. A study of 120 patients with metastatic CRC receiving bevacizumab-based treatment (n=80) or chemotherapy alone (n=40)89 found that high BMI, and visceral and subcutaneous fat areas were significantly associated with absence of response to the bevacizumab-based treatment but not the chemotherapy group 89.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it can be speculated that patients with obesity might exhibit an impaired response to chemotherapy, particularly protocols that include targeted therapies. In addition, in some patients with obesity, increased plasma levels of insulin may further decrease therapeutic effect 88. A study of 120 patients with metastatic CRC receiving bevacizumab-based treatment (n=80) or chemotherapy alone (n=40)89 found that high BMI, and visceral and subcutaneous fat areas were significantly associated with absence of response to the bevacizumab-based treatment but not the chemotherapy group 89.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin has been shown to cause resistance to chemotherapy in certain colon cancer cell lines via activation of the PI3K/Akt pathway. 49,50 For the drug screening assay, hanging drops of HT-29 human colon adenocarcinoma cells were initiated and maintained on a DµF device for 48 h to allow for the formation of compact spheroids. After 48 h of culture, the medium for some spheroids was exchanged for medium containing 500 nM insulin, whereas the remaining spheroids received normal growth medium.…”
Section: Cell Spheroid Culturementioning
confidence: 99%
“…Both E6 and E7 can also activate PI3K/Akt pathway, a well-known survival pathway which plays a key role in many cancers including cervical cancer [19][20][21][22][23][24][25][26] . The activation of this pathway is also associated with drug resistance to chemotherapy [27,28] . It has been demonstrated that Rb and PP2A mediate E6/E7 in activating the PI3K/Akt pathway [18,23,29] .…”
Section: Introductionmentioning
confidence: 99%